Construction and use of 130 mm (5.25 in) flexible disk cartridges for data interchange using modified frequency modulation recording at 7958 ftprad, 3.8 tpmm (96 tpi) on both sides - 8096 British Standards Institution (London : BSI, 1988)
PSZJBL